30 Do PRAMI and CVLPRIT represent real-life experiences of culprit-only PPCI? - a single centre observational study. (24th April 2016) - Jackson, M; Austin, D; Hall, J; Wright, R; Sutton, A; Muir, D; Swanson, N; Carter, J; Williams, P; de Belder, M
Abstract : Introduction: The RCTs, PRAMI 1 and CVLPRIT, 2 have suggested that preventative PCI for multi-vessel disease identified during PPCI improves outcomes with higher rates of cardiovascular events in the culprit-only cohorts. Methods: 1143 consecutive STEMIs at our centre from August 2011–2013 were retrospectively assessed for eligibility to one or both trials. 343 patients would have been suitable for PRAMI and 196 for CVLPRIT; termed 'observational' cohorts. Outcomes were determined from clinic letters, procedure reports and regional blood result reporting with mortality outcomes compared to ONS data. Results: Over 36 months, our observational PRAMI cohort experienced fewer combined primary outcomes (13.9% vs 22.9%), comparable to the preventative PRAMI (Figure 1A ) arm with only 8.5% undergoing additional early planned revascularisation. Our observational CVLPRIT cohort experienced numerically fewer MACE primary outcomes over 12 months (16.8% vs 21.2% Figure 1B ) with 30 day event rates comparable to the preventative PCI cohort, despite only 9.2% undergoing additional early planned revascularisation. Conclusion: Our all-comers culprit-only PCI cohorts have better outcomes than those seen in the published RCTs suggesting a high-risk population may have been selected for inclusion. Reference: PRAMI trial. Wald DS, Morris JK, Wald NJ, et al . Randomized trial of preventive angioplasty in myocardial infarction. N Eng J Med . 2013, 369 (12), 1115–1123 CVLPRIT trial. Gershlick AH. Khan JN, Kelly DJ, et al . Randomized trial of complete versus lesion-only revascularization in patients undergoing primary percutaneous coronary intervention for STEMI and multivessel disease: the CvLPRIT trial. J Am Coll Cardiol . 2015 Mar 17;65 (10):963–972. Figure A was originally published in N Eng J Med, 369(12):1115–1123, D. S. Wald et al, Randomised Trial of Preventive Angioplasty in Myocardial Infarction, Copyright © 2013 Massachusetts Medical Society. All rights reserved. Figure B was originally published in J Am Coll Cardiol, 65(10):963–972, A. H. Gershlick et al, Randomised trial of complete versus lesion-only revascularisation in patients undergoing primary percutaneous coronary intervention for STEMI and multivessel disease: the CvLPRIT trial, Copyright © 2015 American College of Cardiology Foundation.